2016
DOI: 10.1371/journal.pone.0155875
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Gene Biomarker at the Tipping Point of Adaptive and Adverse Responses in Human Bronchial Epithelial Cells

Abstract: Determining mechanism-based biomarkers that distinguish adaptive and adverse cellular processes is critical to understanding the health effects of environmental exposures. Shifting from in vivo, low-throughput toxicity studies to high-throughput screening (HTS) paradigms and risk assessment based on in vitro and in silico testing requires utilizing toxicity pathway information to distinguish adverse outcomes from recoverable adaptive events. Little work has focused on oxidative stresses in human airway for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…In recent years, studies have shown that microarray analysis and deep-sequencing technologies such as RNA-Seq analysis can be exploited to determine adaptive pathways, which regulate responses to stressors (Pillai et al, 2014; Currier et al, 2016; Zheng et al, 2018). Previous microarray studies linking toxicity and adaptive transcriptomic and proteomic responses in green algae, Chlamydomonas reinhardtii , exposed to silver showed that the cells initiate a defense response to combat oxidative stress and eliminate silver via efflux transporters (Pillai et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, studies have shown that microarray analysis and deep-sequencing technologies such as RNA-Seq analysis can be exploited to determine adaptive pathways, which regulate responses to stressors (Pillai et al, 2014; Currier et al, 2016; Zheng et al, 2018). Previous microarray studies linking toxicity and adaptive transcriptomic and proteomic responses in green algae, Chlamydomonas reinhardtii , exposed to silver showed that the cells initiate a defense response to combat oxidative stress and eliminate silver via efflux transporters (Pillai et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Previous microarray studies linking toxicity and adaptive transcriptomic and proteomic responses in green algae, Chlamydomonas reinhardtii , exposed to silver showed that the cells initiate a defense response to combat oxidative stress and eliminate silver via efflux transporters (Pillai et al, 2014). Another microarray study used a similar strategy to identify enrichment in p53 signaling and NRF2-related genes in adaptive and adverse responses to zinc in human bronchial epithelial cells (Currier et al, 2016). For Mn exposures, there is no information on Mn dose-response effects on the gene expression profile with a graded model from non-toxic to toxic exposures.…”
Section: Introductionmentioning
confidence: 99%
“…Total p53 did not demonstrate a clear treatment response in this model system. We have previously observed activation of p53 phosphorylation in the absence of increased levels of total p53 under similar conditions in zinc-treated BEAS-2B cells 14 .…”
Section: Representative Resultsmentioning
confidence: 52%